Camp Midnight - Seagle, Steven T. (Image Comics, 2016)
When Skye accidentally boards the wrong bus to summer camp, she ends up at Camp Midnight, where everyone except Skye and her new friend Mia is a full-fledged monster. Skye must keep her identity as a human hidden until she can finally catch the bus that will take her back home.